Pelatihan Peningkatan Kemampuan Komputer Guru Yayasan Mathlaul Anwar Satu Dalam Rangka Menunjang Proyek Penguatan Profil Pelajar Pancasila - Kadafi, Abdul Rahman; Santoso Setiawan; Tuslaela; Indah Purnamasari (Forum Kerjasama Pendidikan Tinggi, 2024)
The Mathla'ul Anwar Satu Foundation is an Islamic educational institution located in Bogor, West Java. This foundation oversees several schools with an Islamic religious background. Teachers who teach at the Mathla'ul Anwar Satu Foundation are faced with the problem of an independent curriculum initiated by the Ministry of Education. The teachers who teach at the Mathla'ul Anwar Satu Foundation do not fully understand the implementation and application of the independent curriculum for students. The lack of ability to use technology-based devices means that teachers at the Mathla'ul Anwar Foundation have not been able to prepare interactive and optimal materials and learning materials. Based on this, community service was created in the form of MS Office Training to Support the Project for Strengthening the Profile of Pancasila at the Mathlaul Anwar Satu Foundation. The implementation of this community service takes the form of counseling on the use of MS Office in strengthening the profile of Pancasila for the implementation of the independent curriculum for students. By holding this activity, it is hoped that it can help Mathla'ul Anwar Satu Foundation teachers understand the independent curriculum